Level of family support for university students during the COVID-19 pandemic: A case study among students at the University of Malaya, Malaysia - Asbah Razali; Rosya Izyanie Shamshudeen; Nur Azah Razali (Jurnal Sosiologi Dialektika, 2023)
The COVID-19 pandemic has not only brought major changes to the survival of society at large. The spread of this virus also specifically has an impact on university students who are at home during the quarantine period. This study aims to identify the level of family support among the University of Malaya students. This study used a quantitative research method, with 103 respondents/university students from eight faculties at the University of Malaya. Researchers used a quantitative approach to analyze the information data obtained from respondents. In this study, the collected data were analyzed through descriptive analysis methods to determine the level of family support. The results showed that the level of family support was moderate. This shows that the role of the family is also very important for university students during the COVID-19 pandemic. The family is the basis on which individuals depend for survival, where their basic functions include preparing an environment and situation that is suitable for the development of healthy family members physically, mentally, socially, and so on. This study concludes that family presence not only directly influences various aspects of child socialization but also has an important influence on individual mental health.